Architect's pocket book of kitchen design - Baden-Powell, Charlotte, 1936- (Elsevier/Architectural Press, 2005)
Targeted primarily at designers and home owners in the UK. As with the best-selling 'Architects Pocket Book' this title includes everyday information which the architect/designer normally has to find from a wide variety of sources and which is not always easily to hand. Focusing on kitchen design, this book is of use to the student as well as the experienced practitioner. It outlines all the information needed to design a workable kitchen, including ergonomics, services such as water and waste, appliances, and material choices for the floor, walls and ceiling. There is no similar compendium cu.